2017
DOI: 10.22159/ajpcr.2017.v10i5.16648
|View full text |Cite
|
Sign up to set email alerts
|

In VITRO ANTIDIABETIC EFFECTS OF FERULA ASSA-FOETIDA EXTRACTS THROUGH DIPEPTIDYL PEPTIDASE IV AND Α-Glucosidase INHIBITORY ACTIVITY

Abstract: Objective: Diabetes mellitus (DM) causes hyperglycemia, which is one of the most common diseases in the world. One of the strategies for the treatment of diabetes is maintaining postprandial glucose level through inhibition of dipeptidyl peptidase IV (DPP-IV) and α-glucosidase enzymes. The aim of this study was to determine in vitro antidiabetic potential of Ferula assa-foetida via DPP-IV and α-glucosidase inhibitory activities.Methods: F. assa-foetida seeds were extracted in methanol, ethanol, ethanol-methano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…When experiments were undertaken by choosing F. asafoetida to assess DPP-IV inhibition activity using methanol, ethanol, water, and methanol-ethanol as organic solvents, it was observed that, among all the fractions, ethanol and ethanolmethanol fractions showed a maximum inhibitory effect with 24% and 22%, respectively (45).…”
Section: Ferrula Asafetida: In Vitro Inhibition Efficacy Against Dpp-ivmentioning
confidence: 99%
“…When experiments were undertaken by choosing F. asafoetida to assess DPP-IV inhibition activity using methanol, ethanol, water, and methanol-ethanol as organic solvents, it was observed that, among all the fractions, ethanol and ethanolmethanol fractions showed a maximum inhibitory effect with 24% and 22%, respectively (45).…”
Section: Ferrula Asafetida: In Vitro Inhibition Efficacy Against Dpp-ivmentioning
confidence: 99%
“…The F. gummosa essential oil significantly reduced low-density lipoprotein cholesterol and triglycerides in diabetic rats; even though the essential oil tested group did not display any significant difference in glucose level from the diabetic group. Yarizade et al,(2017) studied the antidiabetic activity of F. assafoetida. In this study, it was observed that F. assa-fetida showed its antidiabetic activity by inhibiting a-glucosidase and DPP-IV (Dipeptidyl peptidase-IV).…”
Section: Hypoglycemic and Hypolipidemic Effectmentioning
confidence: 99%
“…Ferula assa-foetida is an herbaceous plant of the Apiaceae family and has a number of medicinal properties. The ethanolic fraction of F. assa-foetida inhibited DPP-4 activity by 24.5% [ 103 ].…”
Section: Ddp-4 Inhibitors From Natural Sourcesmentioning
confidence: 99%